Comparative Study of New Re-Ni-Mo/Al2o3 and Conventional Hydrodesulphurization Catalyst - Mohammed, Abdul Halim A. Karim; Hussein, Hussein Qasim; Naife, Tariq M. (Iraqi Journal of Chemical and Petroleum Engineering, 2015)
New types of hydrodesulfurization (HDS) catalyst Re-Ni-Mo/ γ-Al2O3 was prepared and tested separately with two prepared conventional HDS catalysts (Ni-Mo/ γ-Al2O3 and Co-Mo//γ-Al2O3) by using a pilot plant hydrotreatment unit. Activities of three prepared hydrodesulfurization catalysts were examined in hydrodesulfurization (HDS) of atmospheric gas oil at different temperatures 275 to 350 °C and LHSV 1 to 4 h-1, the reactions conducted under constant pressure 40 bar and H2/HC ratio 500 ml/ml .Moreover, the hydrogenation of aromatic (HAD) in gas oil has been studied. HDS was much improved by adding promoter Re to the Ni-Mo/Al2O3 catalyst. The results showed that Re-Ni-Mo/ γ-Al2O3 have more activity in desulfurization than Ni-Mo//γ-Al2O3 and Co-Mo/ γ-Al2O3 catalysts. The efficiency of hydrodesulfurization was markedly reduced over the Co -Mo/ γ-Al2O3.Also the result showed that Ni-Mo//γ-Al2O3 have a minimum aromatic content 15.44 %.